2018
DOI: 10.1177/1934578x1801300304
|View full text |Cite
|
Sign up to set email alerts
|

Medical Cannabis for the Treatment of Inflammation

Abstract: The connection between Cannabis sativa's chemical compounds and their ability to treat three different inflammatory ailments including bowel diseases, (IBD, e.g., Crohn's and ulcerative colitis), neuronal diseases (IND, e.g., Parkinson and Alzheimer), and a wide range of inflammatory skin diseases (ISD, e.g., atopic dermatitis and psoriasis) is presented. We review the range of experiments conducted over the last decade using either the whole extract of cannabis or separated mono-phytocannabinoids in the attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 88 publications
(104 reference statements)
0
5
0
4
Order By: Relevance
“…By focusing the attention on hemp nonpsychoactive cannabinoids, CBD has been demonstrated to be useful in the treatment of different inflammatory ailments, including bowel diseases (e.g., Crohn's and ulcerative colitis), neuronal diseases (e.g., Parkinson and Alzheimer), and a wide range of inflammatory skin diseases (e.g., atopic dermatitis and psoriasis) [21].…”
Section: The Chemistry Of Cannabis Sativa Lmentioning
confidence: 99%
See 1 more Smart Citation
“…By focusing the attention on hemp nonpsychoactive cannabinoids, CBD has been demonstrated to be useful in the treatment of different inflammatory ailments, including bowel diseases (e.g., Crohn's and ulcerative colitis), neuronal diseases (e.g., Parkinson and Alzheimer), and a wide range of inflammatory skin diseases (e.g., atopic dermatitis and psoriasis) [21].…”
Section: The Chemistry Of Cannabis Sativa Lmentioning
confidence: 99%
“…As regards cancer, CBD has exhibited antiproliferative and proapoptotic activities, thus demonstrating modulating the tumorigenesis in different types of cancer, including breast, lung, colon, brain, and others [21].…”
Section: The Chemistry Of Cannabis Sativa Lmentioning
confidence: 99%
“…Alternatively, it has been suggested that exogenous cannabinoids may aid in recovery from pain and muscle soreness brought about by PA [43], thereby positively influencing the motivation to engage in PA [46]. Cannabis use has been shown to reduce pain and inflammation among patient populations [47][48][49]. However, among the general population, the evidence for an inverse association between cannabis use and inflammation is limited [31,50].…”
Section: Discussionmentioning
confidence: 99%
“…24 In addition, similar to the results of previous studies, the results of this study showed that the administration of CB2 receptor agonist lipid peroxidation production reversed the GSH consumed, inhibited the expression of TNF-α and IL-1β, and significantly reduced MDA formation in ovarian I/R injury in rats. 10,25 Th e lack of investigation into the contraction responses of the uterine smooth muscle with acetylcholine (from 10−8 to 10−3) and electrical stimulation in an isolated organ bath and the absence of histological examination are the limitations of this study.…”
Section: Discussionmentioning
confidence: 99%